The effect of using integrated learning model on science learning in junior high school: Systematic Literature Review - Sri Aryani; Zarkasih Zarkasih; Radeswandri Radeswandri; Rian Vebrianto (Jurnal Pijar Mipa, 2022)
The implementation of the 2013 curriculum in learning uses a scientific approach, student-centered learning, integrated learning, developing of students' thinking skills, instilling spiritual and social attitudes, as well as exploring students' communication and collaboration skills. Based on the literature review, many schools teach science partially. It turns out that teachers face many obstacles when implementing integrated science learning. One of them is the difficulty of teachers designing integrated science learning models, causing the learning process not to achieve the desired results. It affects students' low learning outcomes and cognitive abilities. Therefore, this study aims to determine the effect and effectiveness of the Integrated Science learning model on science learning in junior high schools. The method used is a systematic literature review using PRISMA diagrams. The database used to search for literature is two digital libraries, namely Google Scholar and Mendeley. Literature screening was conducted to obtain scientific article publications from 2017 to 2021, which discuss using the Integrated Science learning model in science learning in junior high schools. The results of the scientific article search contained eight articles that would be analyzed and synthesized. The analytical technique used is the narrative method by grouping the extracted data. The results of this study affect students due to the use of the Integrated Science learning model, namely in terms of learning outcomes, 21st-century skills, and attitude competence. The use of the Integrated science learning model has proven to be effective in the science learning process in junior high schools.